Scaling of Anatomically Derived Maximal Bite Force in Primates. Issue 7 (18th October 2019) - Deutsch, Ashley R.; Dickinson, Edwin; Leonard, Kaitlyn C.; Pastor, Francisco; Muchlinski, Magdalena N.; Hartstone‐Rose, Adam
ABSTRACT: By combining muscle architectural data with biomechanical variables relating to the jaw, we produce anatomically derived maximum bite force estimations for 23 species of catarrhine and platyrrhine primates. We investigate how bite force scales across the sample as a whole (and within each parvorder) relative to two size proxies, body mass and cranial geometric mean, and the effect of diet upon bite force. Bite force is estimated at three representative bite points along the dental row: the first maxillary incisor, canine, and third‐most mesial paracone. We modeled bite force by combining calculated physiological cross‐sectional area of the jaw adductors from Hartstone‐Rose et al. [Anat Rec 301 (2018) 311–324] with osteological measurements of lever‐ and load‐arm lengths from the same specimens [Hartstone‐Rose et al., Anat Rec 295 (2012) 1336–1351]. Bite force scales with positive allometry relative to cranial geometric mean across our entire sample and tends toward positive allometry relative to body mass. Bite force tends toward positive allometry within platyrrhines but scales isometrically within catarrhines. There was no statistically significant scaling difference with diet. Our findings imply an absence of a dietary signal in the scaling of bite force, a result that differs from the scaling of physiological cross‐sectional area alone. That is, although previous studies have found a dietary signal in the muscle fiber architecture in these species, when these are combined with their leverages, that signal is undetectable. On the parvorder level, our data also demonstrate that the platyrrhine masticatory system appears more mechanically advantageous than that of catarrhines. Anat Rec, 2019. © 2019 American Association for Anatomy Anat Rec, 303:2026–2035, 2020. © 2019 American Association for Anatomy